Comparing Heuristic and Simulation Methods Applied to the Apparel Assembly Line Balancing Problem - KAYAR, MAHMUT (INST CHEMICAL FIBRES, 2016)
In this study, general information on assembly line and simulation and researches on assembly line balancing are theoretically analysed. Afterward time studies with respect to blouse production, which will be analysed in assembly line balancing, are conducted and information, which is necessary for assembly line balancing, is obtained. In parallel with the data obtained, the assembly line is firstly balanced by the Hoffman method, which is one of the heuristic methods. Then the assembly line is balanced again using the Arena Simulation program and results which belong to two different assembly line balancing resolutions are given. The aim of the study is to create an assembly line which has highest line efficiency by using an optimum number of machines and operators as well as highlight the applicability of the Hoffman method to ready-to-wear assembly lines.
Keywords: assembly line balancing; simulation; clothing industry; Hoffman method; heuristic line balancing; INDUSTRY